2017
DOI: 10.1093/asj/sjw275
|View full text |Cite
|
Sign up to set email alerts
|

Resident and Program Director Perceptions of Aesthetic Training in Plastic Surgery Residency: An Update

Abstract: Despite improvements observed from 2008 to 2011 published surveys, there are still challenges to be met especially in facial cosmetic procedures. It is suggested that resident clinics and cadaver courses be universally adopted by all training programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 19 publications
2
49
0
Order By: Relevance
“…Data from both surveys were analyzed using SPSS (IBM, Armonk, N.Y.). Results were also compared to the most recent cosmetic surgery survey completed by Hashem et al 9 to determine differences in cosmetic training over the previous year. Categorical variables were analyzed using Pearson’s chi-square test and Fisher’s exact test, whereas continuous variables were examined using the unpaired Student’s t test and Mann-Whitney U test.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from both surveys were analyzed using SPSS (IBM, Armonk, N.Y.). Results were also compared to the most recent cosmetic surgery survey completed by Hashem et al 9 to determine differences in cosmetic training over the previous year. Categorical variables were analyzed using Pearson’s chi-square test and Fisher’s exact test, whereas continuous variables were examined using the unpaired Student’s t test and Mann-Whitney U test.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies analyzing the quality of aesthetic surgery training have shown deficits in training satisfaction and low confidence in performing common cosmetic procedures upon graduation. 2 , 3 , 8 , 9 This is not only limited to the United States but also Europe and Canada. 4 , 10 More specifically, in 2006, a survey by Morrison et al 3 determined that 76% of program directors felt that senior residents were satisfied while only 51% of residents admitted to being satisfied with their cosmetic training.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, some variability in cosmetic exposure was noted between respondents. This variability may be explained by the preferences of residency programs and/or program directors whereby different programs may place greater emphasis on reconstructive plastic surgery than aesthetic training [7,10]. Additionally, it is possible that graduates guide their own surgical exposure to some degree and those pursuing other sub-specialties pursue do not seek out as much cosmetic exposure as others who are pursuing an aesthetic-based practice.…”
Section: Table 8 Number Of Graduates (Residents and Aesthetic Fellowmentioning
confidence: 99%
“…This can lead to deficiencies in knowledge [4]. Furthermore, studies demonstrate that program directors often disagree with residents regarding the quality of cosmetic surgery training and the best approach to provide exposure [2,9,10]. Historically, these differences have translated into wide variability in trainees' confidence performing core aesthetic procedures.…”
Section: Introductionmentioning
confidence: 99%